Aseptic nonunion of pediatric subtrochanteric fracture: A case report - Dharmshaktu, Ganesh Singh; Roy, Anshuman Vijay (Indian Journal of Child Health, 2015)
Nonunion of pediatric fractures related to the extracapsular proximal femur is a rare event if managed appropriately. Varus malposition renders increased stress over the fracture site leading to failure of the sound union. Management of such fractures is difficult owing to limited implant choices and presence of adjacent open physes. Open reduction and freshening of edges, removal of fibrous tissue, internal fixation with intra, or extramedullary implants, and a compliant follow-up are keys to the good functional outcome.